Hot water incorporated with salicylic acid dips maintaining physicochemical quality of Holland' papaya fruit stored at room temperature - Suriyan Supapvanich; Surassawadee Promyou (My University, 2017)
The effects of hot water incorporated with salicylic acid (SA) dips on quality of 'Holland' papaya fruit stored at room temperature (30±2ºC) was investigated. The fruit were immersed in 0, 1.0, 2.0 and 3.0 mM SA solutions at 42 ºC for 40 min following at 49 ºC for 20 min and untreated (control). Both hot water and hot SA dips prevented the incidence of fungi during storage. The hot SA dips delayed the fruit ripening including maintaining firmness, skin colour, and total soluble solids (TSS) content. Hot SA dips retarded the weight loss rather than hot water dip and control, respectively. All treatments had no affect flesh colour when compared to the control. Hot SA dips enhanced carotenoids, ascorbic acid and antioxidant content during storage. This work suggest that 2.0 mM hot SA dip is a reliable alternative maintaining quality and enhancing bioactive compounds in the papaya fruit during storage.
Keywords: Flesh; Control sample; Postharvest Quality and Shelf Life Management